2005
DOI: 10.1039/b509345g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalysed aryl amination reactions in supercritical carbon dioxide

Abstract: Palladium catalysed C-N bond formation in supercritical carbon dioxide has been accomplished. Carbamic acid formation is avoided in part through the use of an N-silylamine as the coupling partner. Employing a catalyst system of Pd2dba3(1 mol%) and 2-dicyclohexylphosphino-2',4',6'-triisopropyl-1,1'-biphenyl (X-Phos)(2 mol%) enabled the catalytic amination of aryl bromides and chlorides with N-silylanilines to be realised in excellent yield. Extension of the methodology to the N-arylation of N-silyldiarylamines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 70 publications
1
23
0
4
Order By: Relevance
“…[243] Another area of reaction development has been in the application of supercritical carbon dioxide (scCO 2 ) as solvent for the palladium-catalyzed amination of aryl halides using biaryl phosphine ligands (Scheme 71). [244,245] Holmes showed that for successful reaction to occur in this medium it is necessary to protect the amine with a trimethylsilyl group. The authors hypothesize that this is necessary to prevent carbamate formation from occurring.…”
Section: Development Of Reaction Conditionsmentioning
confidence: 99%
“…[243] Another area of reaction development has been in the application of supercritical carbon dioxide (scCO 2 ) as solvent for the palladium-catalyzed amination of aryl halides using biaryl phosphine ligands (Scheme 71). [244,245] Holmes showed that for successful reaction to occur in this medium it is necessary to protect the amine with a trimethylsilyl group. The authors hypothesize that this is necessary to prevent carbamate formation from occurring.…”
Section: Development Of Reaction Conditionsmentioning
confidence: 99%
“…In path a, the oxidative addition of an aryl halide to Pd 0 species 9 gives ArPdX(Xphos) (10), which generates (ArCOO)PdX(Xphos) (11) in the presence of CO 2 . In path a, the oxidative addition of an aryl halide to Pd 0 species 9 gives ArPdX(Xphos) (10), which generates (ArCOO)PdX(Xphos) (11) in the presence of CO 2 .…”
Section: Direct Carboxylation Of Organic Halides With Comentioning
confidence: 99%
“…[10] In the protocol, the methodology was extended to the N-arylation of N-silyldiarylamines, N-silylazoles, and N-silylsulfonamides. [10] In the protocol, the methodology was extended to the N-arylation of N-silyldiarylamines, N-silylazoles, and N-silylsulfonamides.…”
Section: Nitrogen Nucleophilesmentioning
confidence: 99%
“…N-Methyl-N-phenyl-2-methoxyaniline (Table 3, entry 5) [26]. Pale yellow oil; 1 H NMR: d 7.19-7.12 ( 4H, m), 6.95-6.94 (2H, m), 6.70 (1H, t, J = 7.3 Hz), 6.64-6.62 (2H, m), 3.72 (3H, s), 3.19 (3H, s).…”
Section: General Procedures For the Coupling Reactionmentioning
confidence: 99%